2015
DOI: 10.1002/2013ja019691
|View full text |Cite
|
Sign up to set email alerts
|

Pi2 pulsations observed around the dawn terminator

Abstract: We examined Pi2 pulsations observed simultaneously at low‐latitude stations (L = 1.15 − 2.33) around the dawn terminator. Those Pi2 pulsations observed in the sunlit region were polarized in the azimuthal (D, positive eastward) direction. We found that the D component oscillations in the dark and sunlit regions were in antiphase, whereas the H component oscillated in phase. A statistical analysis indicates that these D component phase reversals occurred about 0.5 h sunward of the dawn terminator at 100 km in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Models based on the fast mode wave [plasmaspheric resonance (e.g., Yeoman and Orr 1989) or the direct driven fast mode wave (e.g., Kepko and Kivelson 1999)] cannot therefore explain the D phase reversal near the terminator. Recently Imajo et al (2015) suggested that the terminator effect could be explained by a change in the contributing currents from the FACs on the nightside to the meridional ionospheric currents on the sunlit side of the terminator, and vice versa. The meridional ionospheric currents are part of the dayside ionospheric current closure, including the equatorial Cowling current (see figure 8 in the 2015 paper).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Models based on the fast mode wave [plasmaspheric resonance (e.g., Yeoman and Orr 1989) or the direct driven fast mode wave (e.g., Kepko and Kivelson 1999)] cannot therefore explain the D phase reversal near the terminator. Recently Imajo et al (2015) suggested that the terminator effect could be explained by a change in the contributing currents from the FACs on the nightside to the meridional ionospheric currents on the sunlit side of the terminator, and vice versa. The meridional ionospheric currents are part of the dayside ionospheric current closure, including the equatorial Cowling current (see figure 8 in the 2015 paper).…”
Section: Discussionmentioning
confidence: 99%
“…If only a sharp gradient of conductivities is considered, the terminator effects are almost the same at dawn and dusk. However, case studies by Imajo et al (2015) showed that the distributions of wave properties with respect to the location of the terminators are not the same, although similar D component phase reversals were also found on the dusk side. A more detailed understanding of the differences between the effects of dawn and dusk terminators may provide clues to the determination of geometrical differences in currents.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations